Variable resistance training reduces blood glucose levels in octogenarian elderly women (Research, Society and Development, 2021)
Introduction: The use of resistance training with variable resistance (RTVR) on biodynamic factors has been explored in the scientific literature, however information on RTVR use in long-income diabetic elderly is still inconclusive in the literature. Objective: To analyze the acute effect of variable resistance training with elastic bands on blood glucose levels of octogenarian older women. Method: Seven octogenarian older women (81.4 ± 1.61 years of age) diagnosed with type two diabetes mellitus participated in the study. Resting blood glucose was measured 10 minutes before and 10 minutes after a session of resistance exercises with variable resistance using elastic bands. Results: After the RTVR, blood glucose levels (effect size: 2.49; p